Comparative global burden analysis of lymphoma subtypes: a statistical evaluation of severity across global regions - Liang, Yu; Tang, Yingying; WanYan, Yuanyuan; Li, Erwei (Frontiers in Public Health, 2025)
IntroductionVarious subtypes of lymphoma, including Hodgkin lymphoma, non-Hodgkin lymphoma, and Burkitt lymphoma, impose a significant global health burden. This study aimed to analyze the severity of these lymphoma types across different global regions from 1990 to 2021, focusing on age-standardized incidence rates, disability-adjusted life years (DALYs), and the Quality of Care Index (QCI).MethodsData were collected from the Institute for Health Metrics and Evaluation (IHME). Global regions were categorized according to their socio-demographic index (SDI), and trends in death rates, DALYs, and case numbers of various lymphoma subtypes were examined over a 31-year period. The Analysis of Variance (ANOVA) test was employed to compare mortality and DALYs among regions.ResultsThe analysis revealed significant global and regional trends in lymphoma burden. For Hodgkin lymphoma, DALYs decreased from 0.000513 to 0.000285, and the death rate declined from 0.000629 to 0.000313. In contrast, non-Hodgkin lymphoma exhibited an increase in DALYs from 0.002012 to 0.002430 and in deaths from 0.003182 to 0.003624. Notably, in low SDI regions, a marked increase in DALYs was observed for Hodgkin lymphoma (from 0.000396 to 0.000922) and non-Hodgkin lymphoma (from 0.001147 to 0.002779), with statistical analyses confirming higher mortality rates in these areas.DiscussionThese findings highlight significant regional disparities in the severity of lymphoma. While high-income regions demonstrated lower mortality rates due to better healthcare infrastructure, low-income areas experienced higher mortality, underlining the inequality in healthcare access. The results underscore the urgent need for targeted healthcare interventions and specialized treatment strategies to reduce the global lymphoma burden, particularly in under-resourced regions.